PERANCANGAN APLIKASI ANDROID PENJUALAN BARANG DAN JASA BERBASIS E-COMMERCE PADA PIXELS COMPUTER CILEGON BANTEN - Gunawan, Waliadi; Nuryani, Ely; Prasetya, Median (Jurnal Ilmiah Sains dan Teknologi, 2018)
Pixels Computer is one of the start up effort which stand in the Computer division of cilegon area. Its system has walked, but still not effective in the marketing yet. The consument want to get the facilitator or get speed about the relevan inform to get easy going for all their activities the one of is ordering or buying the things and servicing which is bargained by pixels computer.The purpose of this research is to help consument in order able to shop in anywhere and anytime what they wantwith flexible.The aims from this research is to make e-commerce android application about sell things and service by pixels computer. The build this system, the writer use waterfall method, where technic to call actof th data which is used is a style to look of system is directing up to present. While, in supporting the analysis and this program system is use unified modeling language (UML), the result is from pixels computer research able be conclused that with is made it e-commerce android application about sell things and service can make easy the consument in carry out transaction and get inform is needed about product are bangained by pixels computer.